US presidential election 2024: Consequences for fiscal policy - Kimberly A. Clausing (EconPol Forum, 2024)
The Trump Administration enacted deficit-financed tax cuts, and the Trump campaign has proposed doubling down on that approach. The Biden-Harris Administration added less to national debt and shows more commitment to fiscal responsibility. The Trump Administration consistently enacted tax policies that make the tax system less progressive, giving disproportionate tax cuts to those at the top of the income distribution; candidate Trump has proposed multiple new policies that would move in the same regressive direction. The Biden-Harris Administration has consistently proposed (and in some cases, enacted) tax policies that would make the tax system more progressive. A potential Harris Administration is more likely to prioritize strengthening corporate taxation, addressing climate change, and fully funding the IRS. In contrast, a possible second Trump Administration is more likely to lower corporate taxes, reduce IRS funding, and back away from climate change commitments. The Trump campaign has emphasized that large tariffs will be an important part of their tax policy portfolio; this would harm the US economy, reduce job creation, and redistribute tax burdens toward those lower in the income distribution. Such massive tariffs would also damage international relations and risk waves of retaliation. In contrast, the Biden-Harris Administration has emphasized that tariffs have distortionary and regressive impacts. Trump Administration tax policy priorities would have large negative spillover effects on the rest of the world. Harris Administration tax policy priorities would avoid such collateral damage, more productively engaging with partners abroad on global collective action problems.
Keywords: 330